The risk of under-nutrition in hospitalised Malaysian children: use of 3-minute nutrition screening-paediatrics (Paediatric 3-MinNS) - Pei Sien Yeo; Hazreen Abdul Majid (Journal of the Pakistan Medical Association)
Objective: To evaluate the under-nutrition risk of children admitted to hospitals using a validated tool.